Ekplorasi Taman FSRD ISI Denpasar Dalam Seni Instalasi - Dwi Kartika, I Gusti Kade; Karja, I Wayan; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
This thesis contains a description of the creation of installation art with the title Exploration of FSRD ISI Denpasar Park in Installation Art. Based on the experience gained while studying at ISI Denpasar. By practicing sensitivity in his work, the author conducts exploration in the garden of FSRD ISI Denpasar in order to explore ideas and get material for discussion in the creation of installation art. This creation uses the Warih Wisatsana creation method as a writer and curator of fine arts, starting with basic research, exploration, experiments or sketches, embodiment, and dissemination. It takes exploration of in-person interviews to create conceptual installation art. The materials used in this creation are cloth, by adopting the Balinese wastra concept and adding color strokes to the cloth. The technique used in the installation art is assembling by arranging materials into other materials, with a length of 270 meters of cloth stretching in the garden of FSRD ISI Denpasar. The response from nature makes this installation art will produce significant changes. In addition, this installation art work has been responded by ISI Denpasar students by adding materials that have been prepared, so the creation of this installation art is included in participatory art because of the intervention of other people in the installation art. In the end, it can be concluded that art is not only enjoyed with a pair of disembodied eyes, art is also able to bring the audience involved in it.